Knowledge, attitude, and practice of materiovigilance among nurses at a tertiary care hospital in South India: A cross-sectional study - Kiruthika Sivagourounadin; Priyadharsini Rajendran; Mirunalini Ravichandran (Wolters Kluwer Medknow Publications, 2022)
Background and Objective: Inadequate knowledge and underreporting of medical device-associated adverse events (MDAEs) were observed among health-care professionals (HCPs) in studies carried out in other countries. In India, HCP's knowledge, attitude, and practice (KAP) regarding materiovigilance have not been explored extensively. Hence, the present study was carried out to assess KAP of materiovigilance among nurses working in a tertiary care teaching hospital in South India. Materials and Methods: This is a descriptive, cross-sectional study conducted among nurses. A self-administered, validated questionnaire was distributed to 420 nurses. Data were analyzed using the Statistical Package for the Social Sciences software version 21.0. Kruskal-Wallis test was used to compare KAP score of materiovigilance among the study participants. Results: A total of 400 (95.2%) responses were received. About 65.7% (n = 263) of nurses were having adequate knowledge about the various aspects of materiovigilance and 80.5% (n = 322) of nurses had a positive attitude toward MDAE reporting. However, only 18 (4.5%) of nurses have reported about MDAEs. Further, factors such as uncertainty on how to report a MDAE and concerns about their legal issues significantly led to underreporting of MDAEs. Conclusion: The transition of adequate knowledge and positive attitude to good practice of MDAE reporting was lacking among the study participants. Hence, with due consideration of these deficits and the various factors influencing MDAE reporting, it is necessary to conduct periodical workshops and training sessions for HCPs to enhance their spontaneous reporting of MDAEs.